Can personal experience of cancer in a spouse, relative or close friend impact on the professional practice of a nurse? - Noonan, Victoria (2012)
Background: Cancer is a relevant topic at this time as there have been many structural and policy changes in the NHS regarding this area. Personal experience of nurses outside of practice is a concept that has received little investigation, although the small amount of literature available does talk about it in the cancer context. There is a large amount of literature regarding carers of cancer patients but does not acknowledge that these carers may also be nurses. Aim: To find out how personal experience of cancer in a spouse, relative or close friend has an impact on professional practice. Methods: Registered nurses studying in the School of Nursing were recruited for interview. The interviews were semi-structured and asked questions about the respondents’ personal experiences of cancer and how this has influenced them in their lives and work. These interviews were transcribed and then analysed using a qualitative method. Themes emerged and were presented in the findings. Findings: Four core themes relevant to the research question were found from the data; personal experience can improve general nursing skills, personal experience can improve interactions with patients, personal experience can improve interactions with patients’ relatives, and personal experience can cause difficulties in the role of the nurse. Two other themes not identified by the research question were also found; overlaps between professional and the personal, and personal experience of cancer as a child can influence nursing practice. Conclusions: Although nurses are already encouraged to reflect on their personal experiences in professional practice, this new evidence suggests that it is also beneficial to reflect on personal experiences outside of practice. This study has shown that although personal experience of cancer in a relative or close friend can cause difficulties, there are also many positive influences on nursing practice.